The influence of principal managerial and work motivation toward teacher performance - Paruq, Umar; Arafat, Yasir; Putra, Alhadi Yan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Study aims to determine managerial influence of principals and work motivation toward teacher performance. Type of research was quantitative study using t-test and F-test. Sample was hundred of teachers. Data collection technique used questionnaire. Data analysis technique used SPSS program. Results of study (1) Principal managerial had significant influence toward teacher performance. This was evidenced by the t-count 13.998 and t-table 1.660; (2) Work motivation had significant influence toward teacher performance according to t-count 2.206 and t-table 1.660; (3) Principal managerial and work motivation had a significant influence toward teacher performance, based on the test results obtained F-count value 4.653 and F-table 3.09. There was a significant influence between principal managerial and work motivation towards teacher performance.